2021
DOI: 10.3389/fnano.2021.711368
|View full text |Cite
|
Sign up to set email alerts
|

2D SnS2 Nanostructure-Derived Photocatalytic Degradation of Organic Pollutants Under Visible Light

Abstract: Wastewater produced by the textile industry contains various dyes and organic compounds that directly or indirectly affect surface water or groundwater pollution. Visible-light-driven semiconductor photocatalysis is the leading pathway for the degradation of environmental pollutants. Herein we report the bottom-up hydrothermal growth of 2D tin disulfide nanostructures (SnS2 NSs) for the efficient photodegradation of organic pollutants such as Rhodamine B (Rh.B) and Methyl Violet (M.V) in an aqueous medium unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The observed binding energies of Sn 3d and S 2p spectra are in good agreement with Sn 4+ and S 2− of SnS 2 . 40 The N 1s spectrum showed that the peak at 402.5 eV corresponds to the N -oxide of the SnS 2 -2 material (Fig. 3d).…”
Section: Resultsmentioning
confidence: 94%
“…The observed binding energies of Sn 3d and S 2p spectra are in good agreement with Sn 4+ and S 2− of SnS 2 . 40 The N 1s spectrum showed that the peak at 402.5 eV corresponds to the N -oxide of the SnS 2 -2 material (Fig. 3d).…”
Section: Resultsmentioning
confidence: 94%
“…Presently, the total number of publications on SnS 2 as a photocatalyst remains at less than 500, significantly lower compared with conventional photocatalysts such as TiO 2 or ZnO, and even other transition metal dichalcogenide (TMD) materials like MoS 2 and WS 2 (based on Scopus data). As a 2D photocatalyst material, SnS 2 has found applications across various domains, including air purification, 44,55 wastewater treatment, 47,84–87 hydrogen production, 88–97 and antibacterial purposes, 41 CO 2 reduction, and 89,91,98–100 nitrogen fixation. 92,94,101…”
Section: Sns2 Properties and Photocatalytic Applicationsmentioning
confidence: 99%
“…The pioneering works on two-dimensional (2D) atomically thin graphene, its derivatives, and the rising graphene quantum dots (GQDs) have enlightened the path for the exploration of other promising quantum materials. , In the post-graphene era, few-to-monolayer, nanocrystals (NCs) or QDs of the layered transition metal dichalcogenide (LTMD) family have attracted the wide attention of the scientific community and have been conceived as the best substitute for 2D graphene and 0D GQDs owing to their excellent optoelectronic behaviors. 2D WS 2 , one of the members of the LTMD family, has gained significant attention owing to its size-tunable band gaps and remarkable optoelectronic properties. , Its single layer possesses several unique properties and has been potentially exploited in the field of optoelectronics, catalysts, transistors, sensors, energy storage, theranostics, and bioimaging. …”
Section: Introductionmentioning
confidence: 99%